2019
DOI: 10.3390/nu11112597
|View full text |Cite
|
Sign up to set email alerts
|

mir-101-3p Downregulation Promotes Fibrogenesis by Facilitating Hepatic Stellate Cell Transdifferentiation During Insulin Resistance

Abstract: Insulin resistance (IR) and microRNAs (miRNAs), which regulate cell-to-cell communication between hepatocytes and hepatic stellate cells (HSCs), may intertwine in nonalcoholic fatty liver disease (NAFLD) pathogenesis. The aim of this study was to evaluate whether epigenetics and environmental factors interact to promote progressive NAFLD during IR. We examined the miRNA signature in insulin receptor haploinsufficient (InsR+/−) and wild-type (wt) HSCs by RNAseq (n = 4 per group). Then, we evaluated their impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 47 publications
2
16
0
2
Order By: Relevance
“…Moreover, Dai L.et al investigated the role of miR-30b in regulating IR in NAFLD, and demonstrated that miR-30b represented not only a potential target for the treatment of IR, but also a non-invasive disease biomarker of NAFLD [19]. Work by Meroni M. et al reported that IR combined with diet-induced liver injury contributes miR-101-3p downregulation, which may promote progressive NAFLD through HSC and hepatocyte transdifferentiation and proliferation [22]. The present results identi ed a novel miR-129-5p to be highly expressed in the serum of NAFLD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Dai L.et al investigated the role of miR-30b in regulating IR in NAFLD, and demonstrated that miR-30b represented not only a potential target for the treatment of IR, but also a non-invasive disease biomarker of NAFLD [19]. Work by Meroni M. et al reported that IR combined with diet-induced liver injury contributes miR-101-3p downregulation, which may promote progressive NAFLD through HSC and hepatocyte transdifferentiation and proliferation [22]. The present results identi ed a novel miR-129-5p to be highly expressed in the serum of NAFLD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Along with genetic predisposition to NAFLD and CVD, disease development and natural history are also modulated by epigenetic mechanisms, heritable but reversible phenomena that modify gene transcription without altering DNA sequence [ 163 ].…”
Section: Genetics and Diet In Nafld And Cardiovascular Diseasementioning
confidence: 99%
“…Moreover, sedentary lifestyle and unhealthy dietary habits may represent paramount environmental risk factors for NAFLD pathogenesis [7]. Hence, its development is closely intertwined with obesity, insulin resistance (IR) and metabolic syndrome features among which atherogenic dyslipidemia and cardiovascular risk [8,9].…”
Section: Introductionmentioning
confidence: 99%